2021
DOI: 10.1371/journal.pone.0253549
|View full text |Cite
|
Sign up to set email alerts
|

An integrated risk and epidemiological model to estimate risk-stratified COVID-19 outcomes for Los Angeles County: March 1, 2020—March 1, 2021

Abstract: The objective of this study was to use available data on the prevalence of COVID-19 risk factors in subpopulations and epidemic dynamics at the population level to estimate probabilities of severe illness and the case and infection fatality rates (CFR and IFR) stratified across subgroups representing all combinations of the risk factors age, comorbidities, obesity, and smoking status. We focus on the first year of the epidemic in Los Angeles County (LAC) (March 1, 2020–March 1, 2021), spanning three epidemic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…Our findings generally agree with published studies and meta-analyses [ 1–21 , 25–34 ] reporting increasing age, male sex, medical comorbidities, and multiple laboratory abnormalities as COVID-19 mortality risk factors. This concurrence supports the concept of a shared set of mortality risk factors among inpatients with COVID-19 irrespective of study population origin.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings generally agree with published studies and meta-analyses [ 1–21 , 25–34 ] reporting increasing age, male sex, medical comorbidities, and multiple laboratory abnormalities as COVID-19 mortality risk factors. This concurrence supports the concept of a shared set of mortality risk factors among inpatients with COVID-19 irrespective of study population origin.…”
Section: Discussionsupporting
confidence: 92%
“…Patients were hospitalized with COVID-19 at Pomona Valley Hospital Medical Center (PVHMC) between March 9, 2020 and April 30, 2021, a period corresponding with 2 initial COVID-19 surges in LAC [ 25 ]. The PVHMC is an accredited 412-bed, not-for-profit, independent, acute care community hospital providing a range of healthcare services in eastern LAC and western San Bernardino County.…”
Section: Methodsmentioning
confidence: 99%
“…Public awareness is the prerequisite to implementing the control interventions for combatting the COVID-19 pandemic; however, such awareness is governed by an individual’s health safety practices and attitudes [ 3 , 22 ]. It is predicted from various epidemiological models that without preventive measures to contain the spread of COVID-19, the world would confront a steep rise in the number of cases [ 23 , 24 , 25 , 26 ]. These scenarios have driven numerous nations to take steps aimed at “flattening the curve” to dodge a sudden surge in COVID-19 cases.…”
Section: Introductionmentioning
confidence: 99%
“…First, as described in many meta-analyses and other factor analysis studies on the CFR, we estimated it using a confirmed case count [38,54,[56][57][58][59][60][61][62][63][64][65][66][67][68]. Confirmatory diagnosis involves ascertainment bias; the elevated CFR during the pandemic's peak may partly be related to the lower frequency of diagnosis, whereas IFR and CFR diverged significantly [55,[69][70][71]. Second, the confirmed deaths could have been smaller than the actual total number of deaths.…”
Section: Discussionmentioning
confidence: 99%